PUBLIC RELATIONS POLITIK DI MEDIA MASSA TELEVISI DALAM DEBAT POLITIK PADA PILPRES 2009 (Studi Kasus pada Tim Sukses Kandidat Capres – Cawapres Megawati Prabowo) - Novita Damayanti (Indonesian Journal of Dialectics, 2012)
Presidential elections 2009 in Indonesia was the most important political communication events of the democractic cycle, Presidential debate are often the primary opportunity for democractic leaders to communicate directly with the citizens they represent. Qualitative research method with a constructive paradigm is used in this research. A case study approach is seen to best describe the political public relations activities in this research. This research is divided into two parts, first, a visual framing analysis on Metro TV and TV one; second, a construction of Megawati-Prabowo's presidential candidacy team and the political public relations meaning of the team. The constructive of reality broadcasted on Metro Tv tries to give an understanding to the Indonesians especially the viewers to become a rational voters on the presidential debate 2009. The constructive of realiaty g of program “Menuju Istana di TV One” is a battle that must be won by one of the parties and was used as a reference for the voters. The constructive meaning used by the team during the 2009 presidential debate served as an opportunity for Megawati-Prabowo to establish a national image, a leader Pro rakyat) by implementing the ekonomi kerakyatan. The efforts campaign team activities are considered as political public relations by the researcher : image management, media management, informational management, internal communication, positioning event management, issue management.